PENGEMBANGAN SITUS SIGAYA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SD - Aditya Kristrifena; Yohana Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to improve the critical thinking skills of fourth grade elementary school students. The subjects in this research were 21 grade IV students at SD Negeri 03 Klepu, Pringapus District. Data collection was carried out by interviews, observation, formulating learning objectives, developing products, product trials, pretest and posttest as well as evaluation and revision. This research method uses quantitative descriptive. The research results show that SIGAYA media can improve the critical thinking skills of fourth grade elementary school students. SIGAYA Media obtained a score of 100% in material expert validation and 100% in media expert validation. Both validation results are included in the